MAPK Phosphatase-1 Deficiency Exacerbates the Severity of Imiquimod-Induced Psoriasiform Skin Disease - Zhao, Weiheng; Xiao, Shuxiu; Li, Hongjin; Zheng, Tingting; Huang, Jian; Hu, Ran; Zhang, Baohua; Liu, Xinguang; Huang, Gonghua (Frontiers in Immunology, 2018)
Persistent activation of mitogen-activated protein kinase (MAPK) is believed to be involved in psoriasis pathogenesis. MAPK phosphatase-1 (MKP-1) is an important negative regulator of MAPK activity, but the cellular and molecular mechanisms of MKP-1 in psoriasis development are largely unknown. In this study, we found that the expression of MKP-1 was decreased in the imiquimod (IMQ)-induced psoriasiform mouse skin. MKP-1-deficient (MKP-1–/–) mice were highly susceptible to IMQ-induced skin inflammation, which was associated with increased production of inflammatory cytokines and chemokines. MKP-1 acted on both hematopoietic and non-hematopoietic cells to regulate psoriasis pathogenesis. MKP-1 deficiency in macrophages led to enhanced p38 activation and higher expression of IL-1b, CXCL2 and S100a8 upon R848 stimulation. Moreover, MKP-1 deficiency in the non-hematopoietic compartments led to an enhanced interleukin-22 receptor signaling and higher expression of CXCL1 and CXCL2 upon IMQ treatment. Collectively, our data suggest a critical role for MKP-1 in the regulation of skin inflammation.